World Health Statistics 2013 (World Health Organization, 2013)
World Health Statistics 2013 contains WHO's annual compilation of health-related data for its 194 Member States and includes a summary of the progress made towards achieving the health-related Millennium Development Goals (MDGs) and associated targets. This year it also includes highlight summaries on the topics of reducing the gaps between the world's most-advantaged and least-advantaged countries and on current trends in official development assistance (ODA) for health. As in previous years World Health Statistics 2013 has been compiled using publications and databases produced and maintained.